Selective estrogen receptor (ER)β activation provokes a redistribution of fat mass and modifies hepatic triglyceride composition in obese male mice. (15th February 2020) - González-Granillo, Marcela; Savva, Christina; Li, Xidan; Ghosh Laskar, Moumita; Angelin, Bo; Gustafsson, Jan-Åke; Korach-André, Marion
Abstract: Estrogen exerts its action through the binding to two major receptors, estrogen receptor (ER)α and β. Recently, the beneficial role of selective ERβ activation in the regulation of metabolic homeostasis in obesity has been demonstrated, but its importance is still controversial. However, no data are available regarding possible gender differences in response to pharmaceutical activation of ERβ. Male mice were fed a control diet (CD) or a high fat diet (HFD) before being treated with the ERβ selective ligand, 4-(2-(3-5-dimethylisoxazol-4-yl)-1H-indol-3yl)phenol (DIP) in the same conditions as in our recently published paper in female mice. Magnetic resonance imaging and spectroscopy were performed repeatedly in vivo after 6 weeks of diet and after 2 weeks of DIP. Adipose tissue distribution and hepatic triglycerides composition were quantified. HFD-treated males showed a feminization of their fat distribution towards more subcutaneous fat depots and increase total fat content and visceral adipose tissue showed clear browning sites after DIP. Hepatic lipid composition was modified by DIP, with less saturated and more unsaturated lipids and an improved insulin sensitivity. Finally, brown adipose tissue size expended after DIP, due to an increase of the size of the lipid droplets. Our data demonstrate that selective activation of ERβ exerts a tissue-specific and sex-dependent response to metabolic adaptation to overfeeding. Most importantly, together with our previously published results in females, the current findings support the concept that sex should be considered in the future development of obesity-moderating drugs. Highlights: Selective ERβ ligand provokes a feminization of metabolism in obese males. Selective ERβ activation exerts a tissue-specific and sex-specific activity. DIP treatment remodels body lipid distribution and composition.